2012
DOI: 10.2298/gsf111230002k
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon stock in some forest soils in Serbia

Abstract: The content of organic carbon (C) was researched in topsoil layers (0-20 cm) in the most represented soils of forest ecosystems in central Serbia: eutric ranker, eutric cambisol and dystric cambisol. The soils were sampled during 2003, 2004 and 2010. Laboratory analyses included the soil physical and chemical properties necessary for the quantification of the soil organic carbon in organic and mineral layers. Mean values of the soil organic carbon (SOC) stores in organic horizons of the study soils varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Analysis of the organic carbon content in the surface layer (0-20 cm) in the most prevalent soils of forest ecosystems in central Serbia: eutric Ranker, eutric Cambisol, and dystric Cambisol has shown that the mean value of organic carbon for all the tested soils amounts to 5.77 kg m -2 (Kadović et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the organic carbon content in the surface layer (0-20 cm) in the most prevalent soils of forest ecosystems in central Serbia: eutric Ranker, eutric Cambisol, and dystric Cambisol has shown that the mean value of organic carbon for all the tested soils amounts to 5.77 kg m -2 (Kadović et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In Serbia, Kadovič et al (2012) studied the regression dependence between carbon content and soil depth and found a modest correlation for dystric brown soils (25 profiles) and a strong correlation for eutric brown soils (31 profiles) and for eutric rankers (12 profiles).…”
Section: Calculating Organic C Stock On Pedogenetic Horizons (Methods 1)mentioning
confidence: 99%